DEVELOPMENT OF INFORMATIONAL IMMUNITY AS THE KEY TO INCREASING THE INFORMATION CULTURE OF PEOPLE (Conferencea, 2022)
The article deals with the formation of information culture in the framework of the further development of democratic reforms in Uzbekistan. Identified threats to the information security of society.